Atenuação do déficit hídrico em plantas de fisális - Leite, Romeu da Silva (2023)
Water deficit is the main promoter of abiotic stress in plants, whether cultivated or underexploited species, such as physalis. The search for tools that contribute to managing the water deficit and increasing plant tolerance is fundamental for the maintenance of agriculture around the world. Analyzes capable of measuring the effects of water deficit at the biomolecular level, complementing the other physiological assessments has been a demand for researchers. For this, two mitigation strategies were used: plant recovery and chemical priming application against the water deficit (20% of the water storage capacity by soil in vessel). At first, the treatments were applied to plants under water deficit in the soil, in which the application has the purpose of reversing the effects of stress. In a second way, the application of chemical compounds was performed prior to the stressor. In both methodologies the chemical agents were applied via foliar spraying. The water deficit negatively influenced most of the variables analyzed in both methodologies. However, the contribution of nitric oxide was able to attenuate, reverse and act in the recovery of the effects of stress in Physalis angulata L. plants, with improvement in gas exchange, growth and yield. When evaluating chemical priming with nitric oxide and proline, similar responses were observed for the species P. angulata and Physalis peruviana L. Thus, the chemical agents used were able to attenuate the effects of water deficit when supplied in pre-treatment, contributing to the increased plant tolerance to stress.